Linear and nonlinear behaviors of light in a silicon ring resonator - Vanishkorn, B.; Kusalajeerung, C.; Chiangga, S.; Pitukwongsaporn, S.; Jukgoljun, B.; Yupapin, P. P. (My University, 2011)
We have investigated the nonlinear switching characteristics of an optical device using a double-coupler silicon ring resonator in the presence of the linear losses, the Kerr nonlinearity, two-photon absorption, free-carrier-induced absorption and dispersion, and thermo-optic, in which the general features of the nonlinear switching of the throughput and drop port signals are similar to a single-couple ring resonator and nonlinear Fabry-Perot resonator results, respectively. The interesting results of the double-coupler silicon ring resonator are the low switching power conditions and the linear amplification gain, in which the various applications can provide by controlling the input-output characteristic of silicon-based resonators, for instance, by controlling the coupling ratio, free-carrier lifetime, and input wavelength, which can provide the multiple applications for optical switches, logic gates, and memories. © 2011 Wiley Periodicals, Inc.
Keywords: integrated optics; nonlinear switching; optical bistability; ring resonator